Striving toward team-based continuity: provision of same-day access and continuity in academic primary care clinics - Jane H. Forman; Claire H. Robinson; Sarah L. Krein (BMC, 2019)
Abstract Background An important goal of the patient-centered medical home is increasing timely access for urgent needs, while maintaining continuity. In academic primary care clinics, meeting this goal, along with training medical residents and associated professionals, is challenging. Methods The aim of this study was to understand how academic primary care clinics provide continuity to patients requesting same-day access and identify factors that may affect site-level success. We conducted qualitative interviews from December 2013-October 2014 with primary care leadership involved with residency programs at 19 Veterans Health Administration academically-affiliated medical centers. Interview recordings were transcribed verbatim. To analyze the data, we created comprehensive, structured transcript summaries for each site. Site summaries were then entered into NVivo 10 software and coded by main categories to facilitate within-case and cross-case analyses. Themes and patterns across sites were identified using matrix analysis. Results Interviewees found it challenging to provide continuity for same-day in-person visits. Most sites took a team-based approach to ensure continuity and provide coverage for same-day access, notably using NPs, PAs, and RNs in their coverage algorithms. Further, they reported several adaptations that increased multiple types of continuity for walk-in patients, urgent care between in-person visits, and follow-up care. While this study focused on longitudinal continuity, both by individual PCPs or by a team of professionals, informational continuity and continuity of supervision, as well as, to a lesser extent, relational and management continuity, were also addressed in our interviews. Finally, most interviewees reported clinic intention to provide patient-centered, team-based care and a robust educational experience for trainees, and endeavored to structure their clinics in ways that align these two missions. Conclusions In contending with the tension between providing continuity and educating new clinicians, clinics have re-conceptualized continuity as team-based, creating alternative strategies to same-day visits with a usual provider, coupled with communication strategies. Understanding the effect of these strategies on different types of continuity as well as patient experience and outcomes are key next steps in the further development and dissemination of effective models for improving continuity and the transition to team-based care in the academic clinic setting.